O envolvimento ativista como parte do “renomear o vivido”: reflexões sobre experiências femininas pelos ativismos populares - Cessimar de Campos Formagio (Ciências Sociais Unisinos)
This text reflects about the relationship between popular activist involvement and the individual and collective process of naming strange sensations arising from social subordinations that build subalternities perceived in everyday life. In interviews with women, conducted from 2015 to 2017, who had experiences in popular activism in the cities of Campinas and São Paulo, it was perceived that popular activism involvement can be part of a social quest to name anxieties and dissatisfaction related to social norms that weave socializing in public places and in the family. Public dialogues about social issues, made possible by activist meetings, may be a possibility of naming previously sensations that were previously confusing sensations and to strengthen dis-identification in relation to two social regulators present in neoliberal rationality: the discourses/ practices of privatization of public spaces and the family dispositive that centralizes domestic and family care responsibilities for women.